The Influence of Islamic Religious Education Public Courses in Improving Noble Character Students Department of Chemistry Education, Indonesian University of Education - Amandha Rainy; Arwa Haiatul Isni; Fuji Nur Resa; Mohammad Rindu Fajar Islamy (Educan : Jurnal Pendidikan Islam, 2023)
Education has not been able to make every individual have commendable behavior such as rampant violence, drug use, sexual harassment, and the loss of human rights committed by students. Therefore, Islamic Religious Education is aimed at raising human awareness in having faith and piety to Allah SWT and getting used to behavior, attitudes, and views of life that are following the teachings of Islam. The existence of Islamic Religious Education courses at universities aims to grow and increase students' faith in realizing commendable morals, through the provision and cultivation of knowledge, appreciation, and student experience regarding the Islamic religion, so that they become students who not only have general knowledge but also have knowledge about religious values. The method used in this research is qualitative and quantitative research with descriptive methods. Quantitative methods aim to describe the situation objectively by using numbers from data collection. The sample in this study was selected using the consecutive sampling method which is a technique for determining subjects who meet the research criteria within a certain period. The sample used was students from the Department of Chemistry Education at the Indonesian University of Education Class of 2019-2021 who had taken part in teaching Islamic Religious Education. Data collection techniques using primary data like questionnaires via a google form. Based on research, Islamic religious education is a very important lesson for every student to form individuals who have good morals and are not far from moral and religious values.